Modern Retail Marketing Mix Analysis of Customer Loyalty With Buying Decisions as an Intervening Variable - Sugito; Aryani Sairun; Desi Astuti; Megasari Gusandra Saragih (International Journal of Social Science and Business, 2022)
Modern retail has become increasingly ubiquitous in people's daily activities as the times have progressed and globalization has occurred. This is due to changes in people's purchasing habits, with consumers preferring to shop at modern retail markets that offer one-stop shopping and competitive prices over traditional markets where transactions are typically conducted through bartering. This study is to analyze the effect of modern retail marketing mixes on loyalty mediated by buying decisions. The population of this study is all customers of Metro Supermarket, with a total sample 224 respondents. The sampling technique is nonprobability sampling with purposive sampling. The results of the study indicate that product, price, promotion and retail service effect on the buying decision of Metro Pasar Swalayan customers.  Shop design and location effect on the buying decisions of Metro Pasar Swalayan customers. Product, promotion, retail service, Shop design and location effect on the loyalty of Metro Pasar Swalayan customers. Meanwhile, the price had no effect on the loyalty of Metro Pasar Swalayan customers. Buying decision partially mediates the effect of product, price, promotion, and retail service on customer loyalty of Metro Supermarkets. But buying decision does not mediate the influence between shop design and location on customer loyalty of Metro Supermarkets.